Maximizing lifetime of heterogeneous wireless turnable camera sensor networks ensuring strong barrier coverage - My Binh, Nguyen Thi; Thanh Binh, Huynh Thi; Ngoc, Nguyen Hong; Anh, Mai Dang Quan; Phuong, Nguyen Khanh (Journal of Computer Science and Cybernetics, 2021)
Barrier coverage in wireless camera sensor networks (WCSNs) has drawn the attention of research community since it promises an extremely large potential in applications involve movement detection and surveillance. As the battery resources are limited, improving the efficiency of energy is one of the key drivers for prolonging the lifetime of barrier coverage. However, most prior studies on this problem only worked on the networks with homogeneous sensors as well as omni-directional sensing coverage that have not been taken into account in WCSNs research. This paper thus investigates the problem of maximizing the network lifetime to ensure strong barrier coverage for heterogeneous case (MLBC-HWCSN). We formulate the problem, and then propose a Modify Maximum Flow Algorithm (MMFA) consisting of three stages: constructing the flow-network, finding the maximum flow and refining the solution to solve this problem. Experimental results on extensive instances show that the proposed methodology is suitable for the studied problem and more efficient than existing algorithms.